The involvement of student soldiers in the 1947 battle of Palembang as a resource for local history education - Sukardi, Sukardi; Gunarhadi, Gunarhadi; Djono, Djono (Jurnal Cakrawala Pendidikan, 2025)
The focus of this research is the importance of teaching local history, such as the five-day battle in Palembang in 1947. Students do not understand this important historical event, even though the battle took place in the middle of the city, but this local history material has not been widely used as a learning resource in schools. The aim of this research is to determine whether the involvement of student soldiers in the five-day battle in Palembang in 1947 can be integrated as a source for local history learning in schools. Qualitative research method, case study type with a historical approach. Data collection uses field studies, observations, interviews, and document studies. Data validation was carried out by triangulating data sources and theory. Data analysis starts with data presentation, reduction, and conclusion drawing. The five-day battle in Palembang in 1947 involved Indonesian soldiers assisted by the community against the Dutch, who wanted to regain control of Palembang. The involvement of young student soldiers, who were bravely involved directly in the battle, served as health workers, messengers, and public kitchen workers. The involvement of student soldiers in this battle contains historical values of struggle, heroism, and never giving up, so these historical values can be integrated as a source of history learning in schools. Its relevance as a learning resource can be seen in the history curriculum in the material on the struggle of figures in defending Indonesian independence.